SOSIALISASI PENINGKATAN NILAI EKONOMI GETAH DAMAR (Agathis sp) PADA PETANI PENGUMPUL DI DESA HUKUANAKOTA KECAMATAN INAMASOL KABUPATEN SERAM BAGIAN BARAT - Parera, Evelin; Siruru, Herman; Parera, Lydia Riekie (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
Damar resin is one of the non-timber forest product commodities that has high economic value. However, limitations in processing techniques and market access hinder optimal utilization by the community. This community service aims to increase community knowledge which will have an impact on increasing the economic value of damar resin through training in processing and marketing techniques in Hukuanakota Village, Inamosol District. The methods used include training in damar processing techniques, development of processed products, and digital-based marketing assistance. The results showed that the training increased community knowledge which is expected to improve the quality of damar products, which has implications for increasing selling prices and community income.